2010
DOI: 10.1007/s11242-010-9642-4
|View full text |Cite
|
Sign up to set email alerts
|

Microscale Visual Study of End Effects at Permeability Discontinuities

Abstract: The physical effect of multiphase fluid distribution and flow at permeability boundaries has not been fully investigated, particularly at the pore scale (1-100 µm), although such behaviour can significantly affect the overall scaled-up reservoir trapping capacity and production performance. In this article, microscale physical models have been used to qualitatively study the pore scale flow events at permeability boundaries, both high to low and vice versa, to gain a better understanding of the role of these b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 21 publications
0
16
0
Order By: Relevance
“…It will change the flow patterns in immiscible displacements from that observed in miscible displacements, especially at low flow rates where capillary effects dominate viscous effects, (Dawe and Grattoni 1998;Dawe et al 2010), which will be further discussed in Sect. 5.…”
Section: Capillary Pressure Wettability and Heterogeneitymentioning
confidence: 99%
See 1 more Smart Citation
“…It will change the flow patterns in immiscible displacements from that observed in miscible displacements, especially at low flow rates where capillary effects dominate viscous effects, (Dawe and Grattoni 1998;Dawe et al 2010), which will be further discussed in Sect. 5.…”
Section: Capillary Pressure Wettability and Heterogeneitymentioning
confidence: 99%
“…For instance, at saturation discontinuities capillary pressures (interfacial curvatures) can change over a few grain diameters giving rise to large pressure gradients. In homogeneous media, such discontinuities may occur across immiscible displacement fronts and at porous media boundaries, such as end effects (Dawe et al 2010). In heterogeneous media, capillary pressure effects are also created at the boundaries between areas with different properties, such as permeability, porosity or wettability changes (Dawe et al 2010).…”
Section: Capillary Pressure Wettability and Heterogeneitymentioning
confidence: 99%
“…On the other hand, previous studies in which supercritical CO 2 was used indicate a thicker permeation front region with 3 to 13.4 PV injected before CO 2 saturation reached a steady distribution (14,15) . The influence of the sub-core scale heterogeneity was discussed by Perrin et al (14) and Shi et al (15) , and recent studies noted that permeability discontinuities cause saturation discontinuities (18,19) . In this study, a thin laminar structure in a large-diameter sandstone sample can be observed by employing microfocus X-ray CT.…”
Section: Effect Of Thin Laminar Heterogeneity For Co 2 Permeation Promentioning
confidence: 99%
“…During the CO 2 permeation from a higher to a lower porosity region, the boundary forms a temporary barrier to the flow of CO 2 and prevents CO 2 flow until the threshold pressure at the boundary is overcome (18,19) .…”
Section: Effect Of Thin Laminar Heterogeneity For Co 2 Permeation Promentioning
confidence: 99%
“…However, most of them are either based on laboratory core flooding experiment data or field data, and they cannot explain the factors controlling the multiphase flow at pore scale (Dawe et al, 2011;Ofori et al, 2010;Shen et al, 2011). To fill this knowledge gap, a detailed research of gas/water two-phase flow behaviours in coal seams at pore scale is essential.…”
Section: Introductionmentioning
confidence: 99%